Sustainability assessment in higher education institutions: exploring indicators, stakeholder perceptions, and implementation challenges - Najihath Basheer; Vian Ahmed; Zied Bahroun; Chiraz Anane (Discover Sustainability)
Abstract Higher Education Institutions (HEIs) play a critical role in addressing global sustainability challenges and advancing the Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education), SDG 11 (Sustainable Cities and Communities), and SDG 13 (Climate Action), through knowledge creation and dissemination. Despite their potential, the integration of sustainability into HEIs is often hindered by fragmented indicators, stakeholder misalignment, and implementation barriers. This study adopts a mixed-methods approach to identify and validate a comprehensive set of Sustainability Indicators (SIs) tailored to the HEI context, with a case study conducted at the American University of Sharjah (AUS). Derived from an extensive literature review, the indicators were validated through semi-structured interviews with key policymakers, revealing gaps in familiarity with sustainability indicators, financial constraints, technological resistance, and decentralized reporting systems. Participants emphasized the importance of environmental initiatives such as energy efficiency and sustainable procurement, while noting the comparatively limited focus on social equity (SDG 10: Reduced Inequalities) and economic dimensions (SDG 8: Decent Work and Economic Growth). Following this, the Relative Importance Index (RII) was employed to analyze stakeholder perceptions through a survey of 81 stakeholders across three key groups (students, educators, and administrative staff) and to rank the indicators by their perceived impact. The findings reveal significant disparities in stakeholder priorities, underscoring the critical need for alignment across governance, environmental, social, economic, and academic pillars. Additionally, challenges such as cost-sustainability trade-offs and fragmented operations highlight the importance of fostering enhanced institutional communication and establishing centralized frameworks to ensure cohesive and effective sustainability efforts. This research offers actionable recommendations to address these barriers, including fostering targeted awareness initiatives, promoting interdisciplinary collaboration, and customizing sustainability frameworks to institutional contexts. By providing a replicable model, the study aligns institutional strategies with stakeholder needs, contributing directly to global sustainability objectives and reinforcing HEIs' role in advancing the UN SDGs.